A novel in situ multiplex immunofluorescence panel for the assessment of tumor immunopathology and response to virotherapy in pediatric glioblastoma reveals a role for checkpoint protein inhibition. (2nd December 2019) - Bernstock, Joshua D.; Vicario, Nunzio; Rong, Li; Valdes, Pablo A.; Choi, Bryan D.; Chen, Jason A.; DiToro, Daniel; Osorio, Diana S.; Kachurak, Kara; Gessler, Florian; Johnston, James M.; Atkinson, T. Prescott; et al.
ABSTRACT: Immunotherapy with oncolytic herpes simplex virus-1 therapy offers an innovative, targeted, less-toxic approach for treating brain tumors. However, a major obstacle in maximizing oncolytic virotherapy is a lack of comprehensive understanding of the underlying mechanisms that unfold in CNS tumors/associated microenvironments after infusion of virus. We demonstrate that our multiplex biomarker screening platform comprehensively informs changes in both topographical location and functional states of resident/infiltrating immune cells that play a role in neuropathology after treatment with HSV G207 in a pediatric Phase 1 patient. Using this approach, we identified robust infiltration of CD8 + T cells suggesting activation of the immune response following virotherapy; however there was a corresponding upregulation of checkpoint proteins PD-1, PD-L1, CTLA-4, and IDO revealing a potential role for checkpoint inhibitors. Such work may ultimately lead to an understanding of the governing pathobiology of tumors, thereby fostering development of novel therapeutics tailored to produce optimal responses.